DEVELOPMENT OF CREATIVE THINKING IN FUTURE TEACHERS ON THE BASIS OF AXIOLOGICAL APPROACH (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The article is devoted to the issue of developing creative thinking in future teachers based on the axiological approach. The authors examine innovative technologies and methods that occupy an important place in the educational process, emphasizing their significance in enhancing creative qualities. The article presents technologies aimed at developing students' creative thinking abilities through group work, role-play games, baseball methodology, and creation of goal-oriented projects. Additionally, it suggests the use of visualization techniques such as diagrams, charts, and mind maps to further improve students' creative thinking. The conclusion drawn from the information indicates that the application of technologies used to develop creative thinking in teachers, based on the axiological approach, yields high results and assists in educating students as socially responsible individuals.